2001
DOI: 10.1016/s0550-3213(01)00013-x
|View full text |Cite
|
Sign up to set email alerts
|

Conformal four point functions and the operator product expansion

Abstract: Various aspects of the four point function for scalar fields in conformally invariant theories are analysed. This depends on an arbitrary function of two conformal invariants u, v. A recurrence relation for the function corresponding to the contribution of an arbitrary spin field in the operator product expansion to the four point function is derived. This is solved explicitly in two and four dimensions in terms of ordinary hypergeometric functions of variables z, x which are simply related to u, v.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
1,146
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 631 publications
(1,173 citation statements)
references
References 36 publications
27
1,146
0
Order By: Relevance
“…Operators with high scaling dimension are no longer suppressed and the remainder completely dominates the OPE. 8 More precisely, we have…”
Section: Comparison With Generalized Free Theories and Asymptotics Fomentioning
confidence: 99%
See 2 more Smart Citations
“…Operators with high scaling dimension are no longer suppressed and the remainder completely dominates the OPE. 8 More precisely, we have…”
Section: Comparison With Generalized Free Theories and Asymptotics Fomentioning
confidence: 99%
“…8 In this limit, the name remainder should actually be used for the finite sum of operators up to ∆ * . It was found in refs.…”
Section: Comparison With Generalized Free Theories and Asymptotics Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the studies [24][25][26][27] have shown that it is even possible to analytically derive completely generic constraints on the spectrum of CFTs. Numerical works have been possible due to increased computer power in the last decades, and rely crucially on an increased understanding of conformal blocks -see [15,[28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…But a formal non perturbative development of the conformal bootstrap program for the O(N ) models was yet to be developed. With the explicit expressions of the conformal blocks in [43,44] and the subsequent works, it was possible to analyze the modern and conventional bootstrap numerically to find various bounds on the operator dimensions, central charges and coupling constants (i.e. the OPE coefficients) as discussed in [45][46][47][48] and so on.…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%